2012
DOI: 10.1371/journal.pone.0043325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Neuronatin Gene in the Porcine Placenta

Abstract: Imprinted genes play important roles in placental and embryonic development. Neuronatin (NNAT), first identified as an imprinted gene in human and mouse brains, played important roles in neuronal differentiation in the brain and in glucose-mediated insulin secretion in pancreatic β cells. In the pig, NNAT was reported to be imprinted in eleven tissues. Our previous microarray hybridization study showed that NNAT was differentially expressed in Yorkshire and Meishan pig placentas, but the imprinting status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This is in contrast to NNAT, a gene putatively linked with glucose transport in the placenta. 20 In our study, this gene demonstrated a U-shaped relationship to growth, where increased expression indicated risk for both LGA and SGA status, suggesting a more complicated connection to these outcomes, and the potential importance of highly coordinated regulation.…”
Section: Discussionmentioning
confidence: 52%
“…This is in contrast to NNAT, a gene putatively linked with glucose transport in the placenta. 20 In our study, this gene demonstrated a U-shaped relationship to growth, where increased expression indicated risk for both LGA and SGA status, suggesting a more complicated connection to these outcomes, and the potential importance of highly coordinated regulation.…”
Section: Discussionmentioning
confidence: 52%
“…In 2012, the study conducted by Gu et al () also confirmed NNAT as an important protein regulating glucose transportation in the pig placenta through the PI3K‐AKT pathway. While a direct link between NNAT and PI3K‐AKT has not been established in this study, the authors detected co‐expression of NNAT (α and β) and IP3K/AKT on the 75th day of gestation.…”
Section: Cellular Signaling Regulated By Nnatmentioning
confidence: 95%
“…It has been demonstrated that the expression prevalence of each isoform can vary depending on the stage of development, tissue specificity, and cellular homeostatic status. For example, during an early stage of brain development, the α‐isoform is predominantly expressed as compared to β‐isoform (Gu et al, ). In β‐cells of diabetic rodents, NNAT‐α is the isoform preferentially reduced (Chu and Tsai, ).…”
Section: Structure Of Nnat and Regulation Of Nnat Gene Expressionmentioning
confidence: 99%
“…NNAT took roles in neuronal differentiation in the brain13 and increased insulin secretion by regulating intracellular calcium levels and hyperglycemia-induced apoptosis in pancreatic β-cells14. In porcine placenta, NNAT was monoallelically expressed and regulated glucose transporter genes15.…”
mentioning
confidence: 99%